The Use of Clinical Practise Guidelines for Community-Acquired Pneumonia in Hospitals in Atlantic Canada - Samuel G Campbell (Canadian Respiratory Journal)
BACKGROUND: Clinical practice guidelines (CPGs) have been shown to improve the care of patients presenting to hospital with community-acquired pneumonia (CAP) and are considered the 'standard of care'. The extent of adoption of CPGs in Canada is unclear.